Análisis de los factores del Analfabetismo Informático en la Red de Docentes del distrito de la Banda de Shilcayo - Quinteros Tuanama, Jimy Ely (2016)
The following thesis report aims to identify and analyze the factors that cause computer illiteracy among teachers who perform their duties in the Banda Shilcayo district network. The Computer and Digital, illiteracy is the inability to handle new technologies for lack of instruction, one of the greatest contemporary obstacles to access to the employment market, which affects society; and that the person with increasing age, changes their attitudes to meet the management of new technologies. The research was conducted under the correlational descriptive design, using the descriptive statistical technique analysis to be qualitative variables, with data collected through the survey and a self-assessment test for teachers of institutions with numerous student and numerous teacher staff in the educational levels of primary and secondary. Among the conclusions it highlights that the factors that cause computer illiteracy in the District Teacher Network Band Shilcayo are the few hours of learning about computers and limited access to new technologies; because no one has the basic computer equipment. The lack of equipment and poor innovation methodologies with audiovisual aids, somehow, affect their professional performance